Clinical characteristics of COVID-19 patients admitted at the Korle-Bu Teaching Hospital, Accra, Ghana - Adjei, Patrick (Ghana Med J, 2020)
The study examined the clinical characteristics and outcomes of 2019 novel coronavirus disease (COVID-19) infections among hospitalized patients. DESIGN: Study design was a retrospective single-center review of hospital data. SETTING: The study was conducted at the COVID-19 Treatment Center of the Department of Medicine and Therapeutics of the Korle-Bu Teaching hospital in Accra, Ghana. PARTICIPANTS AND STUDY TOOLS: A total of fifty patients with laboratory (rRT-PCR) confirmed COVID-19 infection were involved in the study. A chart review of the medical records of the patients was conducted and the data obtained was documented using a data extraction form. RESULTS: The median age was 53 years and most (36% (18/50)) of the patients were at least 60 years of age. Eighty percent (40/50) of the patients were symptomatic, with cough and difficulty in breathing being the commonest presenting symptoms. The mean duration of hospitalization was 12.3 ± 7.3 days. Hypertension and Diabetes Mellitus were the commonest co-morbidities occurring in 52% (26/50) and 42% (21/50) of patients respectively. Fifty percent of patients developed COVID-19 pneumonia as a complication. The mortality rate was 12% (6/50). CONCLUSION: In this study, SARS-CoV2 infection affected older adults with hypertension and diabetes mellitus being the common comorbidities. Patients with these comorbid conditions should be counselled by their clinicians to strictly observe the COVID-19 prevention protocols to reduce their risk of acquiring the infection. There is a need to pay critical and prompt attention to the management of patients with COVID-19 pneumonia particularly among people with diabetes to improve outcomes. FUNDING: None declared